2017
DOI: 10.1111/1745-9125.12147
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Genes, and Generalizability Across Gender: Effects of Maoa and Stress Sensitivity on Crime and Delinquency*

Abstract: In the current study, we extend the gene-by-environment interaction (cGxE) literature by examining how a widely studied polymorphism, the MAOA upstream variable number tandem repeat (MAOA-uVNTR) interacts with distal and proximal stressors to explain variation in crime and delinquency. Prior research findings have revealed that MAOA-uVNTR interacts with single indicators of environmental adversity to explain criminal behavior in general-population and incarcerated samples. Nevertheless, the genetically modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 79 publications
2
21
1
Order By: Relevance
“…The resulting correlations revealed nonsignificant correlations between MAOA-uVNTR genotype and distal stress (r = .05, p = .313), as well as MAOA-uVNTR genotype and proximal stress (r = −.06, p = .177). Similar to the findings reported by Wells et al (2017), these findings fail to indicate the presence of an rGE between MAOA-uVNTR genotype and stress measures examined in the current study (see Supplementary Table 1). The next step was to estimate a series of Tobit regression models.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…The resulting correlations revealed nonsignificant correlations between MAOA-uVNTR genotype and distal stress (r = .05, p = .313), as well as MAOA-uVNTR genotype and proximal stress (r = −.06, p = .177). Similar to the findings reported by Wells et al (2017), these findings fail to indicate the presence of an rGE between MAOA-uVNTR genotype and stress measures examined in the current study (see Supplementary Table 1). The next step was to estimate a series of Tobit regression models.…”
Section: Resultssupporting
confidence: 77%
“…This state of affairs further underscores the need for adequately powered samples. Taken together, it is reasonable to assume that the size of the sample analyzed in the current study, in addition to the samples analyzed by Wells et al (2017), are all underpowered and thus the cG × E × E effect should be interpreted with caution. This conclusion is all the more compelling in view of the fact that the only statistically significant cG × E effect observed in the present study was in the opposite direction to what is typically reported in the literature.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations